Private life : a novel - Smiley, Jane. (New York : Alfred A. Knopf, 2010)
This is a panoramic portrait that traces the life stages of a passive, avoidant woman, including her sad marriage to a delusional astronomer.
Keywords: United States. -- Navy -- Officers -- Fiction; Officers' spouses -- Fiction; Marriage -- Fiction; Psychological fiction